Α-Synuclein Transgenic Drosophila As a Model of Parkinson's Disease and Related Synucleinopathies. (8th December 2010) - Mizuno, Hideya; Fujikake, Nobuhiro; Wada, Keiji; Nagai, Yoshitaka
Abstract : α -Synuclein ( α -Syn) is a major component of protein inclusions known as Lewy bodies, which are hallmarks of synucleinopathies such as Parkinson's disease (PD). The α -Syn gene is one of the familial PD-causing genes and is also associated with an increased risk of sporadic PD. Numerous studies using α -Syn expressing transgenic animals have indicated that α -Syn plays a critical role in the common pathogenesis of synucleinopathies. Drosophila melanogaster has several advantages for modeling human neurodegenerative diseases and is widely used for studying their pathomechanisms and therapies. In fact, Drosophila models expressing α -Syn have already been established and proven to replicate several features of human PD. In this paper, we review the current research on synucleinopathies using α -Syn Drosophila models and, moreover, explore the possibilities of these models for comprehensive genetic analyses and large-scale drug screening towards elucidating the molecular pathogenesis and developing therapies for synucleinopathies.